2023
DOI: 10.1002/ijch.202300026
|View full text |Cite
|
Sign up to set email alerts
|

Bond Energies of UO+ and UC+: Guided Ion Beam and Quantum Chemical Studies of the Reactions of Uranium Cation with O2 and CO

Abstract: Guided ion beam tandem mass spectrometry was used to examine the kinetic energy dependent reactions of U+ with O2 and CO. In the reaction of U+ with O2, the UO+ product is formed in a barrierless and exothermic process with a reaction efficiency at low energies of k/kcol=1.1±0.2, but increases at higher collision energies. Formation of both UO+ and UC+ in the reaction of U+ with CO is endothermic. 0 K bond dissociation energies (BDEs) of D0(U+‐O)=7.88±0.09 eV and D0(U+‐C)=4.03±0.13 eV were determined by analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 142 publications
2
8
0
Order By: Relevance
“…11 The Th + and U + efficiencies reported here compare well with the ion beam 11,22 and FTICR-MS results from Cornehl et al 38 The FTICR-MS measurements of Gibson and coworkers 1,2 are lower than those observed here with the exception of Pu + and Am + where very inefficient reactions under nominally thermal conditions were observed in the FTICR-MS work. Note that the FTICR-MS measurements of Gibson and coworkers 1,5 are systematically lower than those observed in GIBMS experiments as observed for several reactions with Th + , 13,18,22,40 U + , 23 and Gd + . 14,16 The differences in k / k col between measurements has been previously attributed to a different starting ion electronic energy distribution.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…11 The Th + and U + efficiencies reported here compare well with the ion beam 11,22 and FTICR-MS results from Cornehl et al 38 The FTICR-MS measurements of Gibson and coworkers 1,2 are lower than those observed here with the exception of Pu + and Am + where very inefficient reactions under nominally thermal conditions were observed in the FTICR-MS work. Note that the FTICR-MS measurements of Gibson and coworkers 1,5 are systematically lower than those observed in GIBMS experiments as observed for several reactions with Th + , 13,18,22,40 U + , 23 and Gd + . 14,16 The differences in k / k col between measurements has been previously attributed to a different starting ion electronic energy distribution.…”
Section: Resultsmentioning
confidence: 63%
“…4 is semiquantitative estimating intermediate well depths from Sm + CID reactions 15 and product energies from UO + and PuO + BDEs. 23,39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final values agreed within the experimental uncertainties in the 3 cases in which experimental values were available, but unfortunately these uncertainties ranged from 2.4 to 5.5 kcal/mol. Based on previous investigations, ,, the FPD atomization enthalpies are expected to be accurate to within 3 kcal/mol. Enthalpies of formation were calculated for each species by making use of available experimental heats of formation with FPD atomization enthalpies as well as two different FPD-calculated reaction enthalpies involving UF 6 , UO 2 X 2 , H 2 O, and HX species.…”
Section: Discussionmentioning
confidence: 94%
“…Over the past few years, we have been modifying the Feller–Peterson–Dixon (FPD) composite approach , to address the accurate calculation of the thermochemical properties of actinide-containing molecules. By accounting for correlation effects via the coupled cluster method, inclusion of outer-core correlation, scalar relativity from the outset, and spin–orbit coupling using 2-component or 4-component correlated methods, bond dissociation enthalpies have been obtained that in some instances have rivaled the best experimental values, primarily for Th-containing molecules but also recently including small uranium-containing species. …”
Section: Introductionmentioning
confidence: 99%